Magnetohydrodynamics Free Convection Flow of Incompressible Fluids over Corrugated Vibrating Bottom Surface with Hall Currents and Heat and Mass Transfers - Vincent M. Bulinda; Giterere P. Kang’ethe; Phineas R. Kiogora (Journal of Applied Mathematics)
Magnetohydrodynamics free convection flow of incompressible fluids over corrugated vibrating bottom surface with Hall currents and heat and mass transfers considering heat flux is discussed. The corrugation patterns suggested are sinusoidal in nature. The governing equations are solved by the explicit finite difference numerical method of the forward-time backward-space scheme to obtain the analytical results for velocity, concentration, and temperature profiles. The unsteady resultant velocities, concentration, and temperature for various values of physical parameters are discussed in detail, and it is shown that they have significant effects on the fluid flow, and heat and mass transfers are shown graphically.